Metoda piramid w klasyfikacji obiektów symbolicznych - Gliwa, Małgorzata (Pyramidal Clustering in the Classification of Symbolic Objects, 2009)
The aim of this article is a presentation of properties of the pyramidal clustering which is used to classify symbolic objects. The properties of the pyramidal clustering were compared to the properties of hierarchical agglomerative clustering. The example of using this method to classify the symbolic objects from real dataset was also presented. Calculation was made with the use of SODAS and R programmes. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 307-314